(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Because the malignancy system has been poorly planned thus far, oxidative pressure has been emphatically linked to carcinogenesis. The Fuzzy Expert System (FES) was used in this study to assess the oxidative pressure-related cancer risk of potentially life-threatening oral disorders. The serum data of twenty patients with potentially malignant oral disorders were used for this purpose. This data was fed into FES, which generated the 20 rules based on the knowledge system. Following that, the risk of Oral Cancer (OC) was assessed on a scale of 0 to 100. Following a thorough examination, this study advocates that the current methodology might be castoff as a primary assistance in OC transmission and to create upcoming health decisions in hypothetically malicious oral tissues.